Internal Control Systems And Cash Flow Management In Commercial Banks In Rwanda - Ronald, Wandira; Agaba Moses; Jack , Rugasira (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The study aimed to explore whether internal control practices, such as the control environment, control activities, and risk assessment, can address cash flow management challenges at the Bank of Kigali branches in Gasabo District. A cross-sectional survey design was utilized to collect data from Bank of Kigali branches in Gasabo District and Descriptive statistics was used to present the characteristics of the bank's internal control systems as well as cash flow management indicators. A correlational research methodology was employed to describe and measure the degree of association between internal control systems and cash flow management practices. The analysis of the correlation between cash flow management practices and control activities reveals a robust and statistically significant positive relationship. The significant positive impact of risk assessment, as indicated by its unstandardized coefficient of 0.597 and standardized coefficient (Beta) of 0.491, underscores the importance of robust risk assessment procedures. Keywords: Internal Control Systems, Cash Flow Management, Commercial Banks, Rwanda